Spectrophotometric Determination of Micro Amounts of Copper(II) using Resacetophenone. - RANOAYYA, V.; UMA REDDY, P.; BALAKRISHNA, V.V. (Asian Journal of Chemistry, 2010)
Copper(II) forms a light green colour soluble complex with resacetophenone (2,4-dihydroxy acetophenone) in acetic acid-sodium acetate buffer medium of pH 4.7–5.4 and in aqueous dimethyl formamide solution containing very low concentrations of boric acid. The complex has maximum absorbance at 370 nm. The complex is stable for more than 24 h. Beer's law is obeyed upto 19 ppm of Cu(II) at 385 nm and 400 nm. The effect of various diverse ions is also studied. The method is applied for the estimation of micro amounts of copper in brass sample and the results are found to be in good agreement upto 8 ppm of Cu(II).